2019
DOI: 10.1177/1742395319843172
|View full text |Cite
|
Sign up to set email alerts
|

‘La Vida Normal’: Young people adapting to Type 1 diabetes in Bolivia

Abstract: Objectives To identify challenges and coping strategies of young people with Type 1 diabetes (T1D) and their families in Bolivia through qualitative analysis of interviews with beneficiaries of Centro Vivir con Diabetes (CVCD), a diabetes health center supported by the International Diabetes Federation Life for a Child (LFAC) program. Methods Eighteen young people aged 14–33 and at least one caregiver participated in semi-structured interviews in five cities in Bolivia from May to June 2016. Interviews were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Few studies have investigated this phenomenon using a qualitative approach, and the findings generally reflect and support previously published findings in the rather limited existing literature. Specifically, findings support those of Souris et al and Dickinson and O'Reilly, who suggested that, to many young people, living with T1D is "normal life" 18 and "no big deal". 14 T1D had limited influence on participants' daily lives, and they constantly pursued a "normal" young person's life.…”
Section: Discussionsupporting
confidence: 85%
“…Few studies have investigated this phenomenon using a qualitative approach, and the findings generally reflect and support previously published findings in the rather limited existing literature. Specifically, findings support those of Souris et al and Dickinson and O'Reilly, who suggested that, to many young people, living with T1D is "normal life" 18 and "no big deal". 14 T1D had limited influence on participants' daily lives, and they constantly pursued a "normal" young person's life.…”
Section: Discussionsupporting
confidence: 85%
“…These studies highlight the need for clear guidance and information following a T1DM diagnosis. In Bolivia, Souris et al (2019) found that living with T1DM is simply “normal life” for many children and adolescents, but individuals varied in how they achieve this normalcy. While some adapted their lives to accommodate diabetes management, others resisted changes such as diet adaptation, perhaps as a coping mechanism prompted by fears of stigma.…”
Section: Introductionmentioning
confidence: 99%